2018
DOI: 10.1055/s-0038-1676543
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Narcotic Analgesics on the Ultrastructure of the Eyeball (Experimental Study)

Abstract: Background The use of opioids among people of the young and working age has sharply increased in recent years simultaneously with the outbreak observed in the general population. Objective To determine the trigger mechanism of the destructive effect of narcotic analgesics on the ultrastructural level of the vascular tunic of the eyeball. Methods: This experimental study was performed on 26 male rats aged 3.0 months and body weight 160–180 g with daily intramuscular injection of Nalbuphine hydrochlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…The study of microscopic and electron microscopic level revealed the pattern of primary lesion of the vascular component. This prompted the study of angioarchitectonics to evaluate the microcirculatory bed [7,14].…”
Section: Discussionmentioning
confidence: 99%
“…The study of microscopic and electron microscopic level revealed the pattern of primary lesion of the vascular component. This prompted the study of angioarchitectonics to evaluate the microcirculatory bed [7,14].…”
Section: Discussionmentioning
confidence: 99%
“…To date, a considerable number of experimental studies have been conducted on the feasibility and effectiveness of narcotic analgesics and their destructive effects on organs and systems [15,16,17]. There is also no consensus in the current literature on the timing of use and the occurrence of irreversible changes [18,19,20,21].…”
Section: морфологія / Morphologymentioning
confidence: 99%
“…На сьогоднішній день проведена чимала кількість експериментальних досліджень щодо доцільності та ефективності застосування наркотичних анальгетиків, про руйнівний вплив на органи та системи [15,16,17]. У сучасній літературі також немає єдиної думки щодо термінів застосування та виникнення незворотних змін [18,19,20,21].…”
Section: мета дослідженняunclassified
“…
It is known that opioids are effective drugs in the symptomatic treatment of chronic pain of various etiologies, but have a toxic effect with prolonged use [4,17,19]. Current issues for now are the study of morphofunctional changes in various organs under the influence of opioids [9,14,20]. Currently, there are works that highlight the changes in the biochemical parameters of the blood when using narcotic analgesics in the experiment [10,13].
…”
mentioning
confidence: 99%